2014
DOI: 10.1111/ropr.12069
|View full text |Cite
|
Sign up to set email alerts
|

The Determinants of Salience of Energy Issues

Abstract: Studies show that salience of an issue influences the behavior of political elites, policy responses, and the attitudes of the public. Yet while the effects of salience are given considerable attention, less is known about the factors that produce salience. Specifically, what are the determinants of an issue's salience? We examine salience of energy issues in the United States over the past six decades and make two contributions. First, we provide systematic explanations of issue salience. Second, contrary to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 46 publications
0
9
1
Order By: Relevance
“…Therefore, this finding cannot be compared with other studies. While previous research has shown that focusing events increase salience of the energy issue (Lowry and Joslyn, 2014), this study demonstrates that pre-event salience affects public opinion change after a focusing event. The results further indicate that effect of salience on opinion change is a direct, rather than a mediated, effect.…”
Section: Discussioncontrasting
confidence: 78%
“…Therefore, this finding cannot be compared with other studies. While previous research has shown that focusing events increase salience of the energy issue (Lowry and Joslyn, 2014), this study demonstrates that pre-event salience affects public opinion change after a focusing event. The results further indicate that effect of salience on opinion change is a direct, rather than a mediated, effect.…”
Section: Discussioncontrasting
confidence: 78%
“…Energy policy is a rather distant issue for many people: energy literacy (Brounen et al, 2013) and knowledge of the functioning of energy policies (Stadelmann-Steffen and Dermont, 2018) have been shown to be rather low. 3 Moreover, the energy issue often commands a lower priority than more salient issues (Lowry and Joslyn, 2014) like migration or unemployment. 4 Yet, for some groups, energy policy may be highly visible and proximate, which should strengthen the link between existing policies and these individuals’ policy preferences.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…Salient issues affect the interests of a larger part of the public and are also more prominent in the policy agenda (Gormley, ; Lowry and Joslyn, ; Rasmussen et al ., ). They are therefore likely to be relevant to the constituencies of a wider range of interest groups, which increases the potential benefits of participating.…”
Section: Introductionmentioning
confidence: 99%